MO343: Deep Analysis of The AKI—CKD in Allogeneic Stem Cell Transplantation—A Big Data Approach. (3rd May 2022) - Brüder, Nicole; Kielstein, Jan T; Heinze, Luca-Marie; Lück, Catherina; Panagiota, Victoria; Dammann, Elke; Köhler, Sophia; Talbot, Steven; Stadler, Michael; Heuser, Michael; Ganser, Arnold; Eder, Matthias; et al.
Abstract: BACKGROUND AND AIMS: Acute kidney injury (AKI) is a common complication in allogeneic stem cell transplantation (SCT). Although short-lived, i.e. < 90 days, in the majority of patients renal injury can persist for more than 3 months fulfilling the criteria of chronic kidney disease (CKD). So far, only a few publications have shown robust data based on larger patient populations. The aim of this project is to analyse the incidence and severity of AKI in the context of an allogeneic SCT and the transition into CKD. METHOD: Over a 17-year period, 1394 allogeneic stem cell transplants were performed at our tertiary center. Of those, 42 were second transplants. For 1387, a detailed history of creatinine ( n  = 142 563) and eGFR ( n  = 96 689) could be extracted from the Enterprise Clinical Research Data Warehouse. The classification of the respective AKI stages was based on the current KDIGO classification relying solely on the changes in serum creatinine. For AKI, an increase in serum creatinine of ≥ 0.3 mg/dL (26.5 µmol/L) within 48 h or an increase in serum creatinine to ≥ 1.5× baseline within 7 days was used. Persistence of impaired renal function beyond day 90 was defined as CKD. For the analysis of big data and classification of the AKI/CKD an algorithm was programmed. Validation of the results was performed using a colour-coded visualization of renal function (Fig. 1 ). RESULTS: Between 1 January 2003 and 31 December 2020, 239 252 values for creatinine and eGFR were enriched for 1387 transplantations for a period between day –28 before today + 118 after allogeneic stem cell transplantation. The overall incidence of AKI was 86% ( n  = 1199). A total of 993 patients (83%) have shown an AKIN 1, 173 (14%) an AKIN 2 and 33 (3%) an AKIN 3. Of those, 122 (13%) patients died before day + 90 after allogeneic stem cell transplantation and were therefore excluded from CKD analysis. For 271 of 833 patients (33%), the transition to chronic kidney disease has been observed. Further information on patient characteristics, underlying disease, transplant coordinates and related complications and relapse mortality are shown in Table 1 . CONCLUSION: AKI after SCT is the rule and not the exception. As the vast majority of patients show AKIN 1, it might be often clinically overlooked. However, early intervention might mitigate the development of long-term renal impairment. Automated detection (AKI alert systems) as well as identification and subsequent avoidance of factors contributing or aggravating injury (e.g. conditioning, immunosuppression, perfusion, tissue edema, inappropriate dosing of drugs) might minimize long-term renal complications in allogeneic SCT.